Moving from responsibility learning inaction to 'responsibility learning-in-action': A student-educator collective writing on the 'unnoticed' in the hidden curriculum at business schools. Issue 3 (July 2023) - Chatrakul Na Ayudhya, Uracha; Edmondson, Michelle; Harris, America; Littel, Fabien
We are a student–educator writing collective that have come together outside the formal classroom to experiment with 'writing differently', imbued with a desire to enact collective resistance against 'unnoticed' and intentionally hidden aspects of the business school curriculum that condone, normalize and reproduce social injustice and inequalities. As students and educator located in the Department of Organizational Psychology at a UK-based business school, we see our non-traditional writing and inquiry through collective writing as a form of resistance against hegemonic scientific norms of knowledge production that dominate our discipline. We evoked Freire's problem-posing education through a collective enactment of 'responsibility learning-in-action' by participating in regular 'writing as resistance' sessions, where we wrote around our lived experiences of the 'unnoticed' and intentionally hidden curriculum and responsibility learning in the same virtual space and time and then read aloud to one another. Our coming together through this practice (re)claims relationality and solidarity in the student–educator relationship, which is in itself a contribution to the topic of the intersections between responsibility learning and the hidden curriculum at business schools.